Condition assessment of corrosion damaged approach jetty exposed in marine environment - A case study - Srinivasan, P.; Bhaskar, S.; Parivallal, S.; Kesavan, K.; Ravisankar, K.; Venugopal, G. (Journal of Structural Engineering, 2025)
Corrosion of reinforcement in reinforced concrete and pre-stressed concrete in marine environment is amajor durability problem which affects its service life. The chloride intrusion into the concrete from the marine atmosphere causes corrosion of reinforcement and the prestressing wires. An approach jetty structure in marine environment consisting of Prestressed Concrete girders were damaged after 15 years of exposure and it was rehabilitated by shotcreting. Subsequently the repaired structure exhibited damage due to corrosion after a period of 12 years from the time of repair. A detailed systematic assessment was made with nondestructive and partially destructive tests. The residual stresses present in the girders were also determined based on core-trepanning technique. Based on the test results, the jetty structure was strengthened and rehabilitated. This paper presents the details of the test methodology and interpretation of test results.